Functional Characterization of Facilitative Glucose Transporter 4 With a Delay Responding to Plasma Glucose Level in Blunt Snout Bream (Megalobrama amblycephala) - Liang, Hualiang; Maulu, Sahya; Ji, Ke; Ge, Xianping; Ren, Mingchun; Mi, Haifeng (Frontiers in Physiology, 2020)
Facilitative glucose transporter 4 (GLUT4) plays a central role in mediating insulin function to increase glucose uptake in glucose metabolism homeostasis. In this study, the function and localization of GLUT4 in blunt snout bream (Megalobrama amblycephala) were first investigated, and then, the response measured as carbohydrate level, was analyzed. The results showed that the cDNA sequence of GLUT4 in blunt snout bream (MaGLUT4, GenBank accession no: MT447093) was 2868 bp in length, and the corresponding mRNA contained a 5’-UTR region of 513 bp and a 3’-UTR region of 837 bp. MaGLUT4 had an open reading frame of 1518 bp and was encoded by 505 amino acids. Its theoretical isoelectric point and molecular weight was 6.41 and 55.47 kDa, respectively. A comparison of these characteristics with BLASTP results from the NCBI database showed that MaGLUT4 had the highest homology with Cypriniformes fish, with MaGLUT4 and GLUT4 of other Cypriniformes clustered in the phylogenetic tree with other GLUT1-4 amino acid sequences. Compared with the results from the homo_sapiens and mus_musculus data sets, some mutations were observed in the GLUT4 amino acid sequence of these aquatic animals, including an FQQI mutation to FQQL, LL mutation to MM, and TELEY mutation to TELDY. MaGLUT4 was constitutively expressed in the muscle, intestine, and liver, with the highest mRNA level observed in muscle. Furthermore, the predicted tertiary structure and results of immunohistochemical staining showed that MaGLUT4 was a transmembrane protein primarily located in the plasma membrane, where it accounts for 60.9% of the total expressed, according to an analysis of subcellular localization. Blood glucose level peaked within 1 h, and the insulin level peaked at 6 h, while the mRNA and protein levels of GLUT4 showed an upward trend with an increase in feeding time and decreased sharply after 12 h. These results confirmed that MaGLUT4 was mainly distributed in muscles and crosses the cell membrane. The changes in the insulin, mRNA, and protein levels of MaGUT4 lagged far behind changes in blood glucose levels. This delay in insulin level changes and GLUT4 activation might be the important reasons for glucose intolerance of this fish species.